Educação e jovens em medida socioeducativa de semiliberdade: um desafio ao educador no cotidiano educacional na cidade de São Paulo. - Guedes, Miriam Aparecida (2014)
The objective of this dissertation is to deepen the knowledge in the area of education and youth placed in semiliberty socio educational measure in the Metropolitan Regional Divisions of East, West and North under the responsibility of the Foundation Center for Socio-Educational Care for Adolescents - CASA/SP Foundation , linked to the Department of Justice and Defense of Citizenship, State Government of São Paulo - SP, embracing the average age group 17-18 years and enrolled in public state and municipal elementary school in the city of São Paulo - SP. To facilitate the intended discussion, we conducted a literature review on the subject, highlighting studies of Passetti (1985), Zaluar (1992), Priore (1996), Abramo (1997), Volpi (1997 and 1998), Brandão (1997), Bazilio, Earp, Noronha (1998), Freire (2000 and 2005), Marcílio (2001), Boris (2003), Spganol (2005), Sposato (2006), Fonseca (2007), Castro (2009), Junqueira (2009), Castilho (2010), Malvasi (2012). There was as well an analysis of institutional documents, Caderno de Gestão das Medidas Socioeducativas Meio Aberto (2006), - notebook Management of Socio-Educational measures Half Open (2006) and Caderno de Diretrizes para a Implantação da Medida Socioeducativa de Semiliberdade (2006 e 2008), - Note Guidelines for the Implementation Measure of Socio Free range (2006 and 2008) - and interviews in Service Centers of Dawn Free range, Alvorada, Arare, Caetanos and Jacirendi , totaling four young men and two young Call Center Azalea . The study allowed us to characterize the identity of the young author of offense, protagonist of the school setting, playing significant roles in understanding the educational reality in its institutional, cultural and social aspects.